Development and initial validation of the Career Self-Management scale for Chinese coaches - Zhang, Chonghui; Liu, Jing-Dong (Frontiers in Psychology, 2023)
Objective The purpose of the study was to develop and initially validate a context-specific scale assessing Career Self-Management for Chinese coaches (Career Self-Management Scale-CC; CSMS-CC). Methods Firstly, qualitative data obtained from in-depth interview with coaches were contently analyzed to generate potential CSMS-CC items. The content validity of the items was evaluated by a panel of experts. Secondly, the factor structure and item performance of the CSMS-CC were examined using exploratory factor analysis (EFA) and internal consistency reliability of its subscales were evaluated in sample 1 (n = 229, 24.01% females). Thirdly, factor structure of the CSMS-CC was further examined using confirmatory factor analysis (CFA) in sample 2 (n = 295, 32.54% females). Internal consistency reliability was evaluated using Cronbach’ alpha coefficient and composite reliability. Nomological validity was examined using Pearson correlation and structural equation modeling (SEM) by investigating the correlations between CSMS-CC subscales with career success. Finally, measurement invariance and latent mean difference of the CSMS-CC was examined across gender, professional title and coaching class using multiple-group CFA (MGCFA). Results Based on the results of the content analysis and content validity evaluation, 18 CSMS-CC items were retained for further analysis. Results of EFA in sample 1 revealed that eight items were problematic and removed. The second round of EFA revealed that three components were retained and labelled as Networking Behavior (4 items), Training Exploration (3 items), and Guanxi Development (3 items). Results of CFA in sample 2 suggested that the 10-item three-correlated-factors model of CSMS-CC demonstrated acceptable model fit to the data, χ2 = 135.01, df = 32, p < 0.01, CFI = 0.91, TLI = 0.90, SRMR = 0.05, RMSEA = 0.092 (90% CI = 0.076–0.108). Composite reliability (ranging from 0.84 to 0.88) and Cronbach’s alpha coefficients (ranging from 0.78 to 0.81) of three subscales were found satisfactory. Nomological validity was supported by the results that total score and subscale scores of the CSMS-CC were significantly associated with internal marketability and external marketability. It was found that the CSMS-CC measurement model was strict invariant across gender, professional title and coaching class. Significant differences on all three subscales across professional title and on Guanxi development across coaching class were revealed. Conclusion Results of this study provided initial support for the psychometric properties of the 10-item CSMS-CC, which suggested that the CSMS-CC could be used for measuring the career self-management of Chinese coaches.